Testosterone activates glucose metabolism through AMPK and androgen signaling in cardiomyocyte hypertrophy - Troncoso, Mayarling Francisca (2021)
Background: Testosterone regulates nutrient and energy balance to maintain protein synthesis and metabolism in cardiomyocytes, but supraphysiological concentrations induce cardiac hypertrophy. Previously, we determined that testosterone increased glucose uptake—via AMP-activated protein kinase (AMPK)—after acute treatment in cardiomyocytes. However, whether elevated glucose uptake is involved in long-term changes of glucose metabolism or is required during cardiomyocyte growth remained unknown. In this study, we hypothesized that glucose uptake and glycolysis increase in testosterone-treated cardiomyocytes through AMPK and androgen receptor (AR). Methods: Cultured cardiomyocytes were stimulated with 100 nM testosterone for 24 h, and hypertrophy was verified by increased cell size and mRNA levels of β-myosin heavy chain (β-mhc). Glucose uptake was assessed by 2-NBDG. Glycolysis and glycolytic capacity were determined by measuring extracellular acidification rate (ECAR). Results: Testosterone induced cardiomyocyte hypertrophy that was accompanied by increased glucose uptake, glycolysis enhancement and upregulated mRNA expression of hexokinase 2. In addition, testosterone increased AMPK phosphorylation (Thr172), while inhibition of both AMPK and AR blocked glycolysis and cardiomyocyte hypertrophy induced by testosterone. Moreover, testosterone supplementation in adult male rats by 5 weeks induced cardiac hypertrophy and upregulated β-mhc, Hk2 and Pfk2 mRNA levels. Conclusion: These results indicate that testosterone stimulates glucose metabolism by activation of AMPK and AR signaling which are critical to induce cardiomyocyte hypertrophy.